Shibuya, Shinjuku, Ikebukuro : Trois gares á Tokyo - Tiry, Corinne (2002)
Tres estaciones para la línea férrea Yamanote que sirve a la metrópolis.
Keywords: JAPON; TOKYO; TRANSPORTE; URBANISMO; REDES FERROVIARIAS; ESTACIONES DE FERROCARRIL